(untitled) (Journal of Pharmaceutical Negative Results, 2023)
This article engages with the question, whether there is a link between ‘Environmental Sustainability’ and ‘Internationalization of Higher Education’. We try to find an answer to this question with the help of the concept of Instrumentalism (Jonas Stier, 2004). We first consider through literature, the currently prevalent perspectives on ‘Environmental Sustainability’, what it is and why is it required for our race to survive. How ‘Internationalization of Higher Education’ is understood and what motivates countries and universities to promote it. After that, we provide a succinct analysis of how "Environmental Sustainability" is viewed in relation to "Internationalization of Higher Education." We contend that ‘Internationalization of Higher Education’ promotes ‘Environmental Sustainability’